Plasmonic Conglobation of Ultrathin Ag Nanofilms Far below Their Melting Points by Infrared Illumination - Han Dai; Junfeng Zhao; Tongjian Huang; Xinxiang Yu; Jie Sun; Hongjie Fang; Zhenfeng Zhu; Mingfu Zhang; Kun Yu (Applied Sciences, 2018)
Plasmon heating has been employed as a low-temperature annealing method for the conglobation of ultrathin Ag nanofilms into nanoparticles both on silicon and carbon spheres, with complex surface structures, simply under illumination with infrared light. Finite-difference time-domain results provide evidence that the plasmonic light enhancements in the films’ gaps and voids, rather than random surface fluctuations, are the main reason for the conglobation of Ag nanofilms far below the melting point of Ag. This technology can be applied in modern organic optoelectronic devices and photothermal pharma projects to reduce the thermal damage to materials or biological tissues.